LOSS AND DEPRESSION IN JENNIFER NIVEN’S ALL THE BRIGHT PLACES - Rosa Maria Simamora; Riandi Hasibuan (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study discusses loss and depression in Jennifer Niven’s novel, All the Bright Places. The novel represents people who undergo loss and depression because of losing a loved one. This is library research and applies mimetic theory proposed by Abrams saying that literature is an imitation of the real world. The analysis is focused on the loss and depression as a result of the death, neglect, or abandoment. The author creates Violet and Finch to represent people who undergo the situations. Violet losses her beloved sister and suffers from depression of feeling sad and guilty. Finch losses his parents’ figure and care and the worst is he loses his freedom to make friend because of bullying, so he suffers from sadness and depression and ends in commiting suicide. It is found that the author, Jennifer Niven through her novel All the Bright Places conveys that loss can make people depress and affect their lives, and many of them can suffer and live tragically.